Selection of suitable mother wavelet along with vanishing moment for the effective detection of crack in a beam. (15th January 2022) - Kumar, Ramnivas; Nigam, Ravi; Singh, Sachin K
Highlights: Selection of suitable mother wavelet along with vanishing moments for the crack detection in a beam. A relatively low cost photographic method is used for getting the high resolution measurement of the operation deflection shape (ODS) for the localized wavelet based crack detection. Detection of crack near the end supports of the beam. The algorithm is tested for multi-crack detection in the beam. Abstract: Presence of crack in a beam causes a slope discontinuity at the crack location in the operational deflection shape (ODS). Detecting the slope discontinuity in ODS can reveal the presence of crack in a beam. Wavelet transform is a powerful technique to detect discontinuity in a signal. Efficient detection of the crack using wavelet transform depends primarily upon the wavelet family and the number of vanishing moments. In the present work, suitable mother wavelet along with optimum number of vanishing moment is obtained for the effective detection of crack in a beam. Crack detectability is defined to quantify the effectiveness of different mother wavelet and vanishing moments. Finite element analysis is used for getting the simulated ODS. Higher resolution measurement of ODS is the requisite for effective wavelet based crack detection. Photographic method is used for obtaining the high resolution measurement of ODS for the experimental verification. The present methodology works well with the experimentally obtained ODS of the cracked beam. It is capable of detecting crack near the end support also.